Untitled. (Classical Myth & the 'Polifemo' of Góngora, 1989)
The article lists the books published by Scripta Humanistica which includes "The "Comedia" and Points of View," by Everett W. Hesse, "The Story of a Fair Greek of Yesteryear," by James F. Jones, Jr., and "Collapse and Reorganization of the Latin Nominal Flection as Reflected in Epigraphic Sources," by Paul A. Gaeng.